2013
DOI: 10.7824/rbh.v12i2.218
|View full text |Cite
|
Sign up to set email alerts
|

Atividade fisiológica da cana-de-açúcar após a aplicação de herbicidas em pré-emergência

Abstract: Resumo -Objetivou-se neste trabalho avaliar as características fisiológicas da cana-de-açúcar após aplicação de herbicidas em pré-emergência. Para isso, foi conduzido um experimento em esquema fatorial 2x5, onde o fator A constituiu-se das cultivares RB 867515 e SP 81-3250, e o fator B da aplicação em pré-emergência do tebuthiuron, diuron, ametryn, a mistura formulada diuron + hexazinone e uma testemunha sem herbicidas. O delineamento utilizado foi inteiramente casualizado, com quatro repetições. As avaliações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The equilibrium time of tebuthiuron (the concentration of the herbicide in the soil solution becomes constant) was 12 hours for all the used substrates ( Figure 1); this differs from the 7 hour equilibrium time observed by Faria et al (2013) in Brazilian Latosols. The sorption rate depends on the kinetics of the molecule in the soil solution and on the availability of sites that are susceptible to adsorbing the herbicide; soil organic matter is one of the most important herbicide sorption sites (Mirzaei et al, 2013).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The equilibrium time of tebuthiuron (the concentration of the herbicide in the soil solution becomes constant) was 12 hours for all the used substrates ( Figure 1); this differs from the 7 hour equilibrium time observed by Faria et al (2013) in Brazilian Latosols. The sorption rate depends on the kinetics of the molecule in the soil solution and on the availability of sites that are susceptible to adsorbing the herbicide; soil organic matter is one of the most important herbicide sorption sites (Mirzaei et al, 2013).…”
Section: Resultsmentioning
confidence: 66%
“…At this stage, the herbicide is adsorbed by the sites located in the micropores of the soil, but the herbicide molecules that are in the soil solution are repelled by the molecules adsorbed on the surface of the aggregate, reducing the contact between herbicide and micropore spaces. Moreover, the lower herbicide concentration in the soil solution reduces the diffusion of the molecule (Liu et al, 2010;Faria et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…This research also showed that the internal concentration of carbon (Ci) tends to be influenced by factors that reduce the influx of CO2 into the inner space of the leaves due to the decrease in stomatal conductance, however, we obtained promising results with T1-cake, T2 -cake + MAP, T6-cake + MAP + gypsum and T8-cake + MAP + bagasse, causing the plants not to close their stomata, absorbing more light and energy (Ometto et al, 2003;Faria et al, 2013). With regard to sugarcane transpiration (E), our results showed a lower transpiration activity in treatments T1-cake, T4-cake + phosphate and T9-cake + gypsum + phosphate, probably due to soil water restriction and to the ineffectiveness of treatments in mitigating stress (Barboza and Teixeira Filho, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Clorose, necroses foliares e redução do crescimento das plantas são sintomas de intoxicação evidenciados após a aplicação dos herbicidas (ZABLOTOWICZ; REDDY, 2007). Estudos sobre a fisiologia de espécies cultivadas associados, principalmente, às trocas gasosas e à eficiência na utilização da radiação luminosa, que são processos básicos na produção de biomassa, podem indicar os danos provocados pelos herbicidas às plantas (FARIA et al, 2013;SILVA et al, 2014). Dessa maneira, espera-se que a associação das análises fisiológicas com o crescimento das plantas de girassol possa fornecer importantes informações a respeito da sensibilidade da cultura aos herbicidas.…”
Section: Introductionunclassified